2015
DOI: 10.4049/jimmunol.1402424
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Plasma Cells Are a Primary Source of Serum HIV-1–Specific Antibodies in Chronically Infected Individuals

Abstract: Several potent and broadly neutralizing antibodies to HIV-1 have been isolated recently from peripheral blood B cells of infected individuals, based on pre-screening of antibody activity in the serum. However, little is known regarding the cells that make the antibodies that circulate in the blood. Accordingly, we investigated the most likely source, the bone marrow, of chronically HIV-1-infected individuals who were not receiving antiretroviral therapy. Increased frequencies of plasma cells, as well as B cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
(66 reference statements)
2
10
1
Order By: Relevance
“…The bone marrow is the most likely source of serum antibodies, and even in the setting of immune-activating effects of chronic HIV viremia that lead to increased plasmacytosis in tissues and blood, 11,15,58,61,63,96,148,151,160 we have demonstrated that there remains a strong correlation between frequencies of HIV-specific antibodies in the serum and HIV-specific plasma cells in the bone marrow. 69 It is noteworthy that we did not find a correlation between serum levels of HIV-specific antibodies and HIV-specific memory B cells in the peripheral blood. While these analyses were not performed on elite controllers, a study that investigated such a cohort also found a discordance between CD4bsspecific memory B cells in the peripheral blood and antibodies in the serum of the same specificity, with the latter being much lower than the former.…”
Section: Lessons From Elite Controllers and Long-term Non-progressorscontrasting
confidence: 52%
See 2 more Smart Citations
“…The bone marrow is the most likely source of serum antibodies, and even in the setting of immune-activating effects of chronic HIV viremia that lead to increased plasmacytosis in tissues and blood, 11,15,58,61,63,96,148,151,160 we have demonstrated that there remains a strong correlation between frequencies of HIV-specific antibodies in the serum and HIV-specific plasma cells in the bone marrow. 69 It is noteworthy that we did not find a correlation between serum levels of HIV-specific antibodies and HIV-specific memory B cells in the peripheral blood. While these analyses were not performed on elite controllers, a study that investigated such a cohort also found a discordance between CD4bsspecific memory B cells in the peripheral blood and antibodies in the serum of the same specificity, with the latter being much lower than the former.…”
Section: Lessons From Elite Controllers and Long-term Non-progressorscontrasting
confidence: 52%
“…Our previous studies have demonstrated that despite the numerous alterations in B-cell dynamics and differentiation that occur in HIV infection, especially in the setting of chronic HIV viremia ( Fig. 1), there remains a strong correlation between frequencies of HIV-specific plasma cells in the bone marrow and frequencies of HIV-specific antibodies in the peripheral blood (69). These observations suggest that despite HIV-induced aberrant immune activation and dysregulation of B cells, including extensive secondary lymphoid tissue hyperplasia (70, 71), the dynamics of plasma-cell homing to the bone marrow and release of antibody into circulation appear to remain intact.…”
Section: Populations Of Human B Cells and Their Relevance To Hiv Infementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, high numbers of plasma cells were observed at the site of infection for pulmonary TB in non-human primates ( 24 ). The disparity between plasma cell (increased) and total B-cell (decreased) numbers that we observed in HIV-infected TB tissues was also found in the bone marrow of HIV-infected individuals ( 26 ). To explore consequences of increased plasma cells, we measured antibody responses and found increased total IgM and IgG, especially IgG1, in HIV-positive TB patient serum.…”
Section: Discussionsupporting
confidence: 62%
“…Duplicate measurements were averaged. Serum HIV neutralization profiles of breadth and potency were determined against the cross-clade panel of pseudoviruses shown in Supplemental Table 1 and performed by Monogram, as described previously (74). Pools of CD4bs mAbs grouped within each individual source by family or population were also evaluated for potency against the same cross-clade panel of pseudoviruses.…”
Section: Methodsmentioning
confidence: 99%